Listening for understanding - Wolff, Neal (Lincoln : GPN, 1991)
Uses a drama about an advertising account executive to show the need for managers to listen to employees in an empathetic, nonjudgmental manner. Alternate endings reveal different outcomes to problems depending on whether the supervisor was listening in a constructive manner.
Keywords: Communication in personal management; Personnel management